Rice fallows in the eastern India: Problems and prospects - KUMAR, RAKESH; MISHRA, J S; UPADHYAY, PRAVIN KUMAR; HANS, HANSRAJ (The Indian Journal of Agricultural Sciences, 2019)
Rice (Oryza sativa L.) is the most important crop during the kharif in the Eastern India, covering an area of ~26.8 million ha and accounts for ~63.3% of the total rice acreage. Out of which, ~11.7 million ha area in rice production system remains fallow during the succeeding winter season due to several limitations. Efficient utilization of these fallow lands may improve productivity and sustainability of the regions. Soil properties of the region suggests that short duration pulses, i.e. chickpea (Cicer aerietinum), lentil (Lens culinaris), lathyrus (Lathyrus sativa) and oilseeds, viz. safflower (Carthamus tinctorius), linseed (Linum usitatissiumum) and mustard (Brassica campestris) can be grown successfully in rice-fallows with supplemented life saving irrigation. Around 3 million ha extra land under pulses and 1 million ha land under oilseeds can be brought in, with suitable policy interventions. If the location specific constraint to produce the crop are alleviated, these unutilized lands might be converted into the productive lands with crop appropriate planning. This review deals with the problems and prospects of the rice–fallows in the eastern India.